Study protocol: A cross‐sectional study on instrumental support for transitional care among older adults with chronic diseases - Jianing Hua; Xiaoliu Shi; Min Cui; Yuhua Xiao; Juan Xie; Guiling Geng (Wiley, 2021)
Abstract Aims In this paper, we present a study aiming to develop a questionnaire on instrumental support for transitional care as a tool for investigating services, staff, equipment and supplies, and funds of transitional care and conduct a cross‐sectional study on the current instrumental support for transitional care in older adults with chronic diseases. Design A cross‐sectional study combining instrumental support with transitional care through a mixed‐method approach. Methods Data are collected through two sources: distribution of the questionnaire to older adults with chronic diseases and interviews with experts from different specialties such as nursing, clinical medicine, geriatrics, sociology and government. Results The developed questionnaire and expert interviews will be used to investigate the current instrumental support for transitional care among older adults with chronic diseases in China. These findings can help leaders identify areas for improvement in transitional care and contribute to the long‐term positive development of transitional care.